Effect of heparin binding protein and hydrogen peroxide on lipid peroxidation status of bovine sperm cells - Karunakaran, M; Devanathan, T G; Kulasekar, K; Sridevi, P; Jawahar, Tilak Pon; Longanatahsamy, K; Dhali, A; Selvaraju, S (The Indian Journal of Animal Sciences, 2012)
Level of lipid peroxides in frozen thawed bull semen samples was studied in frozen semen straws procured from 22 bulls maintained at bull stations. The semen samples were thawed at 37°C in a water-bath and the level of lipid peroxide was measured by estimating malondialdehyde (MDA) concentration in the semen samples at 0, 60, 120 and 180 min of incubation by thiobarbituric acid assay. 28–30 kDa heparin binding protein (HBP) of sperm membrane @ 25 µg was added to the frozen thawed semen samples and the level of MDA was estimated to check whether addition of HBP of sperm membrane would control the production of lipid peroxides. MDA level (µmol/ml) increased significantly during different periods of incubation-60 min, 120 min and 180 min post thaw in both control and treatment groups. MDA level was significantly lower (P < 0.01) in HBP treated semen sample than control semen at each period of incubation 1.95 vs 2.85; 2.40 vs 3.20; 2.99 vs 4.31 at 60, 120 and 180 min, respectively post thaw. MDA level in H2O2 treated samples increased significantly from 0 min level 1.67±0.1 to 1.85±0.1 at 10 min, 3.05±0.11 at 30 min and to 3.28±0.11 at 60 min incubation. The MDA level in H2O2 treated group (3.28±0.11) was significantly higher than the control (2.85±0.12) and HBP treated group (1.95±0.11) at 60 min incubation period. It was concluded that excessive H2O2 causes significant increases in lipid peroxides level and 28 – 30 kDa HBP of the sperm membrane could help in controlling the oxidative stress of the sperm cells.